Long-term drainage effects on carbon fluxes of an Arctic permafrost ecosystem - Kittler, Fanny (2017)
Permafrost landscapes in the Northern high latitudes with their massive organic carbon stocks are critically important for the global carbon cycle. Large uncertainties in the sustainability of these carbon pools under future climate conditions persist, caused by limited understanding of permafrost carbon cycling processes. A continuous observation program was established near the city of Chersky, NE Siberia, representing a wet tussock tundra ecosystem. Year-round eddy-covariance measurements focused on ecosystematmosphere exchange fluxes of carbon. Recent observations started mid-July 2013, while historic measurements are available for the period 20022005. Since 2004 part of the observation area has been disturbed by a circular drainage ditch, altering the soil water conditions in a way that is expected for degrading of ice-rich permafrost under a warming climate. In comparison to the strong reduction of fluxes immediately following the drainage disturbance in 2005, recent CO2 exchange with the atmosphere over this disturbed part of the tundra indicate a higher carbon turnover, and a seasonal amplitude that is comparable again to that within the control section. By comparing CO2 budgets from the drained and control ecosystems a systematically reduced sink strength within the drained area is found, dominated by increased respiration due to warmer near-surface soil layers. Reduced CH4 emissions are observed under drier and more aerobic conditions resulting in half the efflux from the drained ecosystem in comparison to the control ecosystem. As a net effect of the drainage an increased source of CO2, eq. to the atmosphere indicates a positive effect on global warming. Year-round measurements emphasize the importance of the non-growing season to the annual budget, with substantial contributions during the zero-curtain period representing the re-freezing of the active layer in fall.